JavaScript & jQuery - McFarland, David Sawyer (Missing manual., 2014)
JavaScript lets you supercharge your web pages with animation, interactivity, and visual effects, but learning the language isn't easy. This fully updated and expanded guide takes you step-by-step through JavaScript basics, then shows you how to save time and effort with jQuery--the library of prewritten JavaScript code--and the newest innovations from the jQuery UI plug-in.